Richer, wiser, happier how the world's greatest investors win in markets and life - Green, William (New York Scribner, 2021)
In Richer, Wiser, Happier, William Green draws on interviews that he's conducted over twenty-five years with many of the world's greatest investors, from Sir John Templeton to Charlie Munger, Jack Bogle to Ed Thorp, Will Danoff to Mohnish Pabrai, Bill Miller to Laura Geritz, Joel Greenblatt to Howard Marks. As he discovered, their talents extend well beyond the financial realm. The most successful investors are mavericks and iconoclasts who question conventional wisdom and profit vastly from their ability to think more rationally, rigorously, and objectively. They are master game players who consciously maximize their odds of long-term success in markets and life, while also minimizing any risk of catastrophe. They draw powerful insights from many different fields, are remarkably intuitive about trends, practice fanatical discipline, and have developed a high tolerance for pain. As Green explains, the best investors can teach us not only how to become rich, but how to improve the way we think, reach decisions, assess risk, avoid costly errors, build resilience, and turn uncertainty to our advantage
Includes bibliographical references (pages 257-275) and index.
Keywords: Finance, Personal